PENGARUH PEMAHAMAN AKUNTANSI DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN TERHADAP PELAPORAN KEUANGAN UMKM BERBASIS SAK EMKM - Galuh Condrowati; Utami, Endang Sri; Astuti, Tutut Dewi; Wulandari, Ika (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to determine the effect of understanding accounting and training preparing financial reports on MSME financial reporting based on SAK EMKM. The research method used is a quantitative method. The sample in this study was obtained 33 respondents from 220 SMEs registered in Sragi District, South Lampung Regency. Collecting data in this study using a questionnaire as a research instrument. Data analysis techniques in this study were preceded by instrument tests to prove the validity and reliability of variables, classical assumption tests with normality tests, multicollinearity tests, heteroscedasticity tests, and then hypothesis testing using multiple linear regression tests. The results of the study show that (1) Understanding of accounting has a significant positive effect on the financial reporting of MSMEs based on SAK EMKM (MSMEs registered in Sragi District, South Lampung Regency). (2) Financial report preparation training had no effect on MSME financial reporting based on SAK EMKM (MSMEs registered in Sragi District, South Lampung Regency). The implications of the results of this study for the Sragi District Government of South Lampung Regency can adopt policies related to training in preparing financial reports for MSMEs in Sragi District, South Lampung Regency. For MSMEs, especially in Sragi District, South Lampung Regency, they can increase awareness of understanding accounting and training in preparing financial reports